Recent Advances in GPR Imaging - Laguela, Susana (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The Special Issue (SI) "Recent Advances in GPR Imaging" offers an up-to-date overview of state-of-the-art research activities dealing with the development of Ground Penetrating Radar (GPR) technology and its recent advances in imaging in the different fields of application. In fact, the advances experimented with over the last few decades with regard to the appearance of new GPR systems and the need to manage large amounts of data suggest an increasing interest in the development of new signal processing algorithms and modeling, as well as in the use of three-dimensional (3D) imaging techniques.